KAJIAN PENCAHAYAAN FLOOD LIGHT DI APRON SELATAN BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Yayuk Suprihartini (Politeknik Penerbangan Indonesia Curug, 2019)
Apron is used as an airplane parking lot. In addition to parking,the aircraft’s yard is used to refuel,lower passagers,and fill passangers. The planes is on the air sidewhich directly intersects the terminal building,and is also connected by taxiway that lead to the runway. Where the current condition at the apron I Gusti Ngurah Rai International airport bali lighting system are not good because the intensity has not met the intensity standard recommende by ANNEX volume 14. For this reason, airports need to redesign the results of calculations using LED light so that the intensity of the lighting is in accordance with the standars attachments and have a high level of power efficiency